2020
DOI: 10.1038/s41550-020-1028-0
|View full text |Cite
|
Sign up to set email alerts
|

An ultra-massive white dwarf with a mixed hydrogen–carbon atmosphere as a likely merger remnant

Abstract: White dwarfs are dense, cooling stellar embers consisting mostly of carbon and oxygen 1 , or oxygen and neon (with a few percent carbon) at higher initial stellar masses 2 . These stellar cores are enveloped by a shell of helium which in turn is usually surrounded by a layer of hydrogen, generally prohibiting direct observation of the interior composition. However, 1 arXiv:2003.00028v1 [astro-ph.SR] 28 Feb 2020 carbon is observed at the surface of a sizeable fraction of white dwarfs 3, 4 , sometimes with trace… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 90%
“…More recently, Blouin, Daligault & Saumon (2021) reconciled these results showing that a distillation process during 22 Ne phase separation in crystallizing white dwarfs could explain both the cooling delay of standard white dwarfs and the extra delay experienced by high-mass double white dwarf mergers (see also Bauer et al 2020;Camisassa et al 2021). A number of additional studies have focused on the spectral properties of ultramassive white dwarfs, consolidating the idea that many of these systems are the result of double white dwarf mergers (Hollands et al 2020;Kawka, Vennes & Ferrario 2020;Kilic et al 2021).…”
mentioning
confidence: 90%
“…ONe core white dwarfs are unable to predict these delays. Moreover, the high percentage of observed carbon-rich atmosphere stars (DQ white dwarfs) on the Q branch 20 supports the hypothesis that a large fraction of the white dwarfs on the Q branch would certainly have been formed through merger events 35 .…”
Section: Discussionmentioning
confidence: 67%
“…However, we note that WD J0551+4135 (Gentile Fusillo et al 2019), identified as a potential high-mass, ≈1.15 M e , WD candidate based on its position in the Gaia H-R diagram (Gaia Collaboration et al 2018), occupies a similar location in the H-R diagram to our proposed WD merger remnants (i.e., to the upper left of the standard WD cooling sequence). Hollands et al (2020) argue that the properties of this object are consistent with it having formed from an earlier WD merger. Although WD J0551+4135 is not itself identified in a star cluster, its observed features may provide a clue to the properties of WD merger remnants that may potentially be observed in clusters.…”
Section: White Dwarf Merger Outcomesmentioning
confidence: 63%
“…Although WD J0551+4135 is not itself identified in a star cluster, its observed features may provide a clue to the properties of WD merger remnants that may potentially be observed in clusters. For reference, we show the properties of WD J0551+4135 derived from Hollands et al (2020) as a red star in Figure 10. If indeed a fraction of WD mergers result in young, massive WD remnants, we predict core-collapsed clusters like NGC 6397 may host up to  10 20…”
Section: White Dwarf Merger Outcomesmentioning
confidence: 99%